Nonlinear dynamic analysis of speech from pathological subjects - Jiang, J.J.; Zhang, Yu (Electronics letters, 2002)
Nonlinear dynamic methods are employed to describe the complexity of speech from healthy and pathological subjects with vocal polyps. The analysis demonstrates the low-dimensional dynamic characteristics of normal and pathological voices as well as their statistically significant differences. The potential clinical application of nonlinear dynamics in speech signal processing of pathological voices is suggested.